Profile of Nausea and Vomiting After Sectio Caesarea Surgery with Spinal Anesthesia at ST. Teresa Marampa Hospital - Pither Batu Amba; Amin Susanto; Made Suandik (Jurnal Impresi Indonesia, 2024)
Postoperative nausea and vomiting is a condition that can occur within 24 hours after surgery, and can impact patient harm and cause complications. This study aims to identify the incidence of nausea and vomiting in post-cesarean section patients with spinal anesthesia. This type of research is quantitative with descriptive retrospective research design. Researchers analyzed patient medical records at ST. Teresa Marampa Hospital from January to December 2023, with a sample of 80 respondents using the total sampling technique. The data collection tool used was an observation sheet. Of the 80 respondents, general characteristics based on age showed that most respondents were aged 26-35 years (45 people, 56.3%). Based on labor history, the majority were multiparous (43 people, 53.8%), and 100% of respondents had a history of at term pregnancy. Most respondents did not experience nausea and vomiting (62 people, 77.5%). The profile of nausea and vomiting after cesarean section with spinal anesthesia at ST Hospital. Teresa Marampa Hospital showed that 77.5% of respondents did not experience nausea and vomiting. This finding has important clinical implications, as these results may help in clinical decision making regarding postoperative management. By understanding the profile of nausea and vomiting, medical personnel can design more effective prevention strategies, improve patient comfort, and reduce the risk of complications.